The Education on Personal Financial Management for the Generation Z Personal Fianance Management Education in Tanjung Duren Village, Jakarta - Purwanto, Setiyo; Parashakti, Ryani Dhyan; Frimayasa, Agtovia (Institute of Education and Social Research, 2023)
The young generation is the driving force of a country's economy, such as Indonesia, based on the 2020 population census of 279.2 million people, where the proportion of generation Z reached 27.94%. Where as many young people as Gen Z must be equipped with good financial literacy through financial management knowledge that supports the nation's progress. Universities play an important role in helping society, especially generation Z, by providing financial management education. The contribution of universities plays an active role in helping generation Z understand how to manage their finances effectively. Apart from fulfilling their academic duties, universities also play an active role in applying their professional expertise in the field of economics.The main aim of this community service is to equip generation Z with the importance of financial literacy so that they can use financial resources more optimally amidst very diverse and tempting promotions and consumption offers. Community engagement activities in the Tanjung Duren area of ​​Jakarta, where the majority are generation Z, will be carried out through seminars that focus on long-term financial planning, expenditure analysis and debt management.